Islamic militancy in Bangladeshi newspaper editorials: a discourse analysis - Govindasamy, Subramaniam (2011)
The representation of a religio-political identity by the ‘civil society’ of a country is a complex act intersecting multiple spheres such as the sociocultural, economic, and particularly partisan understanding of religion, politics, and culture dividing the society (and media houses) who inflect, invent, and articulate novel identity for the people of the republic. This study is about how the discursive field of ‘Islamic militancy’ is constructed in Bangladeshi news (print) media. The researchers analyzed 21 texts of editorials published in the month of December 2005 in six Bangladeshi newspapers (in Bangla and English). The analysis has been done following a hermeneutic interpretivist perspective, widely practised in discourse analytical studies. With the rise of militant Islam the faceless militants get their pictures published, and their names appear in national dailies either through complete or vague identification of doers. The analysis shows that most of the editors produced a secular democratic response to the actions perpetrated by the militants. However, their attempt to occupy the contents of the empty signifier of Islam is heavily inflected by their religious predilections; hence, the fight perhaps is never going to be in favor of the secular-democratic politics that the editors